2017
DOI: 10.1158/1078-0432.ccr-16-0844
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Xenograft Establishment from Human Malignant Pleural Mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a rare but aggressive disease with few therapeutic options. The tumor-stromal interface is important in MPM, but this is lost in cell lines, the main model used for preclinical studies. We sought to characterize MPM patient-derived xenografts (PDX) to determine their suitability as preclinical models and whether tumors that engraft reflect a more aggressive biological phenotype. Fresh tumors were harvested from extrapleural pneumonectomy, decortication, or biopsy samples… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 28 publications
3
53
0
Order By: Relevance
“…Using a complementary approach, we treated AC with 10 mM of the GSK3β inhibitor LiCl that inhibited the phosphorylation activity of GSK3β (Supporting Information Fig. S4) and activates Wnt canonical pathway in glioblastoma‐derived cancer stem cells . In LiCl‐treated AC, c‐myc was more translocated into the nucleus (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a complementary approach, we treated AC with 10 mM of the GSK3β inhibitor LiCl that inhibited the phosphorylation activity of GSK3β (Supporting Information Fig. S4) and activates Wnt canonical pathway in glioblastoma‐derived cancer stem cells . In LiCl‐treated AC, c‐myc was more translocated into the nucleus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S4) and activates Wnt canonical pathway in glioblastoma-derived cancer stem cells. 20 In LiCl-treated AC, c-myc was more translocated into the nucleus (Fig. 5a) and more bound to ABCB5 promoter (Fig.…”
Section: The Gsk3β/β-catenin/c-myc Axis Upregulates Abcb5 In Mpm Icsmentioning
confidence: 93%
See 1 more Smart Citation
“…Many of the current studies focus on target therapy to counteract the physio-pathological mechanisms allowing mesothelioma cells to grow in and invade their microenvironment, and to escape from the immune survey. For that purpose, mesotheliomas are developed in so called “mesothelioma models”, which include orthotopic or heterotopic xenografts of human mesothelioma cell lines and patient-derived xenografts in immunodeficient mice [1,2]. Moreover, experimental mesotheliomas models have been developed for different purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advances in establishing the prognostic value of mutational and neoantigenic burden, their value in early-stage NSCLC cases without the treatment of immunotherapies have yet to be explored. In this study, we analyse somatic aberrations found in patient-derived xenograft (PDX) tumors that are representative of patients [19][20][21][22] , in order to evaluate the role and effect of mutation burden and neoantigen load on the prognosis of early stage completely resected NSCLC patients (Figure 1).…”
Section: Introductionmentioning
confidence: 99%